Kenabian Muhammad SAW dalam Perspektif Orientalisme: Sebuah Analisis Kritis (Journal of Comparative Study of Religions, 2023)
The urgency to reassess the Western Orientalism concept is currently recognized by the Islamic community. Orientalism, with its aim to investigate the East and its entire civilization, is a movement with a relatively long history. Originating from concerns about the diminishing role of the church in Western society post-Renaissance, Orientalist thinking stems from a perspective seeking to emphasize studies on the civilizations of the Eastern world. Orientalist thought not only addresses the Eastern world in general but tends to be highly critical of Islam and the civilization developed within it. Therefore, this paper attempts to examine the aspect of Western Orientalist diabolism in scrutinizing and developing criticisms regarding the Prophethood of Muhammad SAW. This represents a thought model synonymous with the Orientalist movement. In its analysis, the researcher presents some unfounded accusations of Orientalism, also providing critiques to address these accusations.